Comparison of physical characteristics and dewatering behaviour between granular and floccular sludges generated from the same sewage source. (June 2019) - Krysiak-Baltyn, Konrad; Cavalida, Raul; Thwaites, Ben; Reeve, Petra J.; Scales, Peter J.; Van den Akker, Ben; Ong, Lydia; Martin, Gregory J.O.; Stickland, Anthony D.; Gras, Sally L.
Graphical abstract: Highlights: The properties of granular and floccular sludges generated from the same sewage source were compared. High resolution electron micrographs show a difference in porosity and microstructure between granules and flocs. The granule surface was covered in spots enriched in sulphur, suggesting an active population of sulphur oxidizing bacteria. Next Generation Sequencing data indicated enrichment of specific SOBs in granular sludge compared to the floccular sludge. Extracted quantitative material properties revealed no difference in dewaterability between granular and floccular sludge. Abstract: Aerobic granular sludge can improve the efficacy of wastewater treatment in existing sequencing batch reactors (SBRs) compared to conventional floccular sludge. Despite the well known advantages of increased capacity, reduced reactor footprint and enhanced nutrient removal, many performance characteristics of granular and floccular sludges have not been directly compared, in particular for sludges generated from treating the same sewage source. In this study we investigated the microstructure, microbial composition, settling and dewatering properties of granular and floccular sludge generated from the same sewage sources. Cryo-scanning electron microscopy analysis indicated that the granular and floccular sludges had a significantly different internal network structure, with flocs being much more open and porous than granules. Sulphur deposits were clearly visible on the surfaces of granules, which was complemented by the enrichment of some sulphur oxidising bacterial species compared to floccular sludge, as assessed by Next Generation Sequencing (NGS). Dewatering measurements showed, as expected, that the settling velocity of granules was much faster than flocs at solids concentrations below the gel point. At at higher solids concentrations above the gel point, however, both flocs and granules form a similar gelled network structure with no significant difference in dewaterability. We used the dewatering properties in process models to predict the impact of granulation on thickener and filter throughput. Overall, this work highlights the biological, structural and physical differences and similarities between granular and floccular sludges with the outcome being improved settling for granules but no significant difference in downstream dewatering properties that pertain to filtration processes.